Self-consistent model of strong coupling theory of electron correlations in disordered crystals - Repetsky, S.P.; Tretyak, O.V.; Vyshivanaya, I.G.; Shastun, V.V. (Успехи физики металлов, 2012)
The method of the description of electron correlations in the disordered crys-tals based on a Hamiltonian of many-particle system as well as the diagram technique for calculation of Green’s functions are developed.